Quantitative risk assessment as a tool to characterize microbiological safety in food. - Roque-Specht, Vânia Ferreira; Castro, João Ernesto Escosteguy; Neto, Miguel Fiod (Revista Gestão da Produção Operações e Sistemas, 2007)
Hazard identification is a process well-known by food industries, and its adequate implementation and execution allow for more efficiency in food safety. There are some methods and tools, which are being currently developed to assist in this process; among them, one can singles out risk evaluation. This article aims at describing details regarding risk evaluation and its incorporation in the process of identification of microbiological hazard. As a case study, it was used the type ‘C’ pasteurized milk produced in Brazil. For this purpose, it was used three databases: 1) properties of the food being studied; 2) the characteristics of the product created; and 3) the characteristics of the microorganisms. The databases were confronted and the results analyzed by the Shell Netica in order to quantify the values concerning the levels of danger of the microorganisms. Of all microorganisms analyzed, only two were classified as ‘high risky’; three were considered moderate risky, and the remaining proved to be of low risk. The present study offers xx subsidies for risk managers - those administrating risks to determine the priorities in the actions for food processing, according to the classification of microrganisms found. Keywords: risk assessment, food safety, milk.